High-temperature abrasion resistance and wear mechanisms of chilled high-chromium cast irons. Issue 1 (May 2021) - Widder, Lukas; Rojacz, Harald; Buscher, Markus; Varga, Markus
Abstract: Hard and highly wear resistant chilled cast irons are of high interest in heavy industries like mining and steel production to achieve durable and sustainable wear protection. In this work a comprehensive view on abrasion mechanisms and the change in microstructure of these materials at elevated temperatures is targeted. Therefore, two different types of commercially available chilled high-chromium white cast irons were chosen. Detailed material characterization and hot hardness tests up to 1000°C were performed to get a first indication of temperature stability. For analysis of abrasive behaviour dry sand/steel wheel testing up to 700°C was conducted. A major part of the work was a thorough examination of the wear tracks and the influence on the microstructure. In the investigated materials chromium carbides Cr(Fe)7 C3 and Mo-rich precipitations are present; the size and stoichiometry depend on the chemical composition. According to the differences in carbide size and type and the respective matrix composition, the hardness and abrasive behaviour changes, especially at higher temperatures. Incorporation of SiC abrasive in the wear zone leads to an in-situ wear protection, which was especially effective at 300°C increasing material's wear resistance compared to room temperature (RT). At higher temperatures up to 700°C it was possible to compensate the hardness loss of the cast iron materials.